Second-generation sequencing of forensic STRs using the Ion Torrent™ HID STR 10-plex and the Ion PGM™. (January 2015) - Fordyce, Sarah L.; Mogensen, Helle Smidt; Børsting, Claus; Lagacé, Robert E.; Chang, Chien-Wei; Rajagopalan, Narasimhan; Morling, Niels
Highlights: STR typing on the Ion PGM™ using the Ion Torrent™ HID STR 10-plex resulted in full concordance for 10 control samples typed in duplicate. Sensitivity: >50 pg. Allele and locus balance was below the current standard for PCR-CE assays. Detection was possible for 20:1 mixtures. This panel was able to produce full profiles for crime case samples from real crime cases where only partial profiles were obtained with the PCR-CE assays. Abstract: Second-generation sequencing (SGS) using Roche/454 and Illumina platforms has proved capable of sequencing the majority of the key forensic genetic STR systems. Given that Roche has announced that the 454 platforms will no longer be supported from 2015, focus should now be shifted to competing SGS platforms, such as the MiSeq (Illumina) and the Ion Personal Genome Machine (Ion PGM™; Thermo Fisher). There are currently several challenges faced with amplicon-based SGS STR typing in forensic genetics, including current lengths of amplicons for CE-typing and lack of uniform data analysis between laboratories. Thermo Fisher has designed a human identification (HID) short tandem repeat (STR) 10-plex panel including amelogenin, CSF1PO, D16S539, D3S1358, D5S818, D7S820, D8S1179, TH01, TPOX and vWA, where the primers have been designed specifically for the purpose of SGS and the data analysis is supported by Ion Torrent™ software. Hence, the combination of the STR 10-plex and the Ion PGM™ represents the first fully integrated SGS STR typing solution from PCR to data analysis. In this study, four experiments were performed to evaluate the alpha-version of the STR 10-plex: (1) typing of control samples; (2) analysis of sensitivity; (3) typing of mixtures; and (4) typing of biological crime case samples. Full profiles and concordant results between replicate SGS runs and CE-typing were observed for all control samples. Full profiles were seen with DNA input down to 50 pg, with the exception of a single locus drop-out in one of the 100 pg dilutions. Mixtures were easily deconvoluted down to 20:1, although alleles from the minor contributor had to be identified manually as some signals were not called by the Ion Torrent™ software. Interestingly, full profiles were obtained for all biological samples from real crime and identification cases, in which only partial profiles were obtained with PCR-CE assays. In conclusion, the Ion Torrent™ HID STR 10-plex panel offers an all-in-one solution from amplification of STRs and amelogenin, and sequencing to data analysis.